The influence of leadership and entrepreneurial orientation on organizational agility mediated by motivation - Antony Sentoso; Cindy Chou; Alden Nelson (Jurnal Fokus Manajemen Bisnis, 2024)
The hotel sector has started to recover after the post pandemic. The sudden change has forced hotel management to respond quickly to market changes. Since the hotel sector interacts directly with consumers, it needs to be extremely flexible in order to enhance product management and improve productivity. Organizational agility enables it to respond to the constantly shifting integrated environment and adapt to new knowledge. The research aims the study of motivation, entrepreneurial orientation, and leadership as factors to increase organizational agility are significant in the hotel industry. The population in this study was hotel employees in Batam, Indonesia. The data collection method used in the research was to create a questionnaire as a medium for collecting data obtained from respondents. In total, 268 responses were collected. The sample selection method used in this research was purposive sampling. This research was tested using the partial least squares with structural equation model. Result of the research shows that both entrepreneurial orientation and leadership has positive effect on motivation and organizational agility. However, motivation has no significant effect on organizational agility. The relationship between entrepreneurial orientation and leadership which motivation as the mediator, doesn’t has a significant effect on organizational agility.